Sketching women: A corpus analysis of woman representation in the Sundanese magazine Manglé (1958-2019) - Susi Yuliawati; Dian Ekawati (Indonesian Journal of Applied Linguistics, 2023)
The media plays a crucial role in shaping gender representation and influencing societal perceptions of gender roles. While several studies have examined the diachronic view of language use in relation to gender representation, there is a dearth of research specifically focusing on the Sundanese language in this line of inquiry. Filling this research gap, the present study aims to analyze the usage patterns of three Sundanese nouns—mojang, pamajikan, and wanoja—that pertain to women, with the goal of exploring the representation of women in the corpus of the Sundanese magazine Manglé. Through a comprehensive corpus-based analysis, this study investigates the frequency and contextual meaning of these nouns using collocation analysis. The analysis encompasses four distinct eras spanning from 1958 to 2019: Guided Democracy, New Order, Transition to Democracy, and Reform. The findings reveal significant shifts in the frequency of these nouns over time. Notably, the usage of the term wanoja has experienced a remarkable increase throughout the examined period, while the occurrences of pamajikan and mojang have undergone a rapid decline. The collocation analysis suggests that women in the Sundanese corpus were initially depicted as dependent individuals, predominantly associated with their traditional roles. However, as the eras progressed, the representation of women evolved, portraying them as increasingly independent and actively engaged in the public sphere. The examination of women's representation in the Manglé corpus offers valuable insights into how women are constructed through lexical choices. It highlights the dynamic nature of female representation, challenging stereotypical gender roles